A Rare Case of Tuberous Sclerosis Complex with Multiple Renal and Lung Masses - Amanpreet Kaur; Mahismita Patro; Sonali Mallik; Amit Goyal (Indian Journal of Respiratory Care)
Tuberous sclerosis complex (TSC) is a neurocutaneous condition marked by the growth of benign hamartomatous tumors across various organ systems. In TSC, pulmonary manifestations encompass multifocal micronodular pneumocyte hyperplasia, lymphangioleiomyomatosis, chylous effusion, and spontaneous pneumothorax. This case report details a 39-year-old female with TSC who presented with a renal mass suggestive of renal cell carcinoma (RCC) and bilateral lung masses suggestive of metastases from RCC 4 years after a right nephrectomy for renal angiomyolipoma. To the best of our knowledge, this is the first case of TSC with RCC presenting with extensive bilateral lung metastases. This case also highlights the need for routine follow-up screening of TSC patients for possible RCC.